138WS The US Institute Of Medicine (IOM) Criteria For Trustworthy Guidelines, The National Guideline Clearinghouse (NGC) And You: A Workshop On NGC's Revised Inclusion Criteria. (15th August 2013) - Nix, M; Jue, J; Haskell, L; Cunningham, S; Coates, V
Abstract : Background: The National Guideline Clearinghouse (NGC), funded by the Agency for Healthcare Research and Quality, will adopt the 2011 IOM revised definition of an evidence-based clinical practice guideline (CPG) and change its criteria for inclusion; thereby raising the bar CPGs must meet in order to be included. Systematic evidence review and benefits and harms of care options are the key changes. Objectives/Goal: At the end of the workshop, participants will be able to recognise the new aspects of the inclusion criteria; understand how the criteria will be applied; apply them to CPGs provided by instructors and estimate eligibility for inclusion; and apply this learning to their organisation's readiness to submit new/updated guidelines to NGC. Target Group, Suggested Audience: Current and future CPG developers; CPG implementers and disseminators; researchers and clinicians. Description of the Workshop and of the Methods used to Facilitate Interactions: This workshop will discuss the revised NGC inclusion criteria and describe specific requirements around a systematic review underpinning the CPG as well as descriptions of benefits and harms. The workshop will include a didactic portion, an interactive exercise, and a take-away checklist. There will be ample question and answer opportunities. Instructors will distribute guidelines and materials and participants will determine eligibility for inclusion in NGC. A checklist will enable participants to understand the changes needed to ensure inclusion of their CPGs in NGC.